Re-thinking men heroes, villains and victims - Synnott, Anthony 1940- (Routledge, 2024)
"Much writing on men in the field of gender studies tends to focus unduly, almost exclusively, on portraying men as villains and women as victims in a moral bi-polar paradigm. Re-Thinking Men reverses the proclivity which ignores not only the positive contributions of men to society, but also the male victims of life including the homeless, the incarcerated, the victims of homicide, suicide, accidents, war and the draft, and sexism, as well as those affected by the failures of the health, education, political and justice systems. Proceeding from a radically different perspective in seeking a more positive, balanced and inclusive view of men (and women), this book presents three contrasting paradigms of men as heroes, villains and victims. Revised and updated, and presenting data and studies from the US, Canada and the UK, it offers a comparative and revised perspective on gender that will be of interest to scholars across a range of social sciences"--
Literaturverzeichnis Seite: 286-300
Keywords: Männer; Männlichkeit; Schurke; Held; Sex discrimination against men; Men / Social aspects; Men in popular culture; Sexism; Discrimination à l'égard des hommes; Hommes / Aspect social; Hommes dans la culture populaire